Clinical characteristics of patients with hepatic steatosis and non-alcoholic steatohepatitis combined with obesity and disorders of the biliary tract, depending on the body mass index. - A. Yu. Filippova (Medičnì Perspektivi)
Nonalcoholic fatty liver disease is now considered as a part of comorbidity pathology. About third part of general population suffers from hepatic steatosis and non-alcoholic steatohepatitis (NASH), which is a serious problem of the XXI century, considering the growth of prevalence of obesity, which leads to fat accumulation in the liver. The aim of our study was to investigate the clinical and functional manifestations of hepatic steatosis and NASH in patients with obesity and disorders of the biliary tract (BT), depending on the body mass index. The study involved 200 patients with nonalcoholic fatty liver disease (NAFLD) (100 patients with hepatic steatosis and 100 NASH) in combination with obesity and BT disorders. Middle age of those examined was 42,1±2,02 years (range from 24 to 73 years). The control group consisted of 30 healthy persons. Each group was divided into subgroups according to body mass index (BMI): overweight (BMI 25-29.9 kg/m2), first degree of obesity (BMI 30-34,9 kg/m2), second degree of obesity (BMI 35-39,9 kg/m2). We evaluated the main clinical and biochemical syndromes (pain, dyspeptic, asthenia, cholestatic, cytolytic, mesenchymal-inflammatory, liver-cell deficiency). It is found, that the most reliable clinical and functional parameters were observed already at the first stage of NAFLD, at the stage of steatosis with fat deposition in the liver. It indicates that the majority of clinical parameters could be considered as early markers of hepatic steatosis formation and its further progression up to the level of steatohepatitis in patients with NAFLD in combination with obesity and BT disorders. Thus, in patients with NAFLD in combination with obesity and BT pathology an active clinical picture of the disease was observed, the severity of which was increasing together with BMI increasing.